2006
DOI: 10.1085/jgp.200509403
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptides and Nitric Oxide Stimulate cGMP Synthesis in Different Cellular Compartments

Abstract: Cyclic nucleotide-gated (CNG) channels are a family of ion channels activated by the binding of cyclic nucleotides. Endogenous channels have been used to measure cyclic nucleotide signals in photoreceptor outer segments and olfactory cilia for decades. Here we have investigated the subcellular localization of cGMP signals by monitoring CNG channel activity in response to agonists that activate either particulate or soluble guanylyl cyclase. CNG channels were heterologously expressed in either human embryonic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 62 publications
(87 reference statements)
5
81
1
Order By: Relevance
“…These findings fit well with previous reports revealing differential effects of pGC and sGC activation on functions within the same cells (26,27). Indeed, recent studies have provided the rationale for such discrepant effects of the two cGMP-generating pathways (28,29).…”
Section: Discussionsupporting
confidence: 92%
“…These findings fit well with previous reports revealing differential effects of pGC and sGC activation on functions within the same cells (26,27). Indeed, recent studies have provided the rationale for such discrepant effects of the two cGMP-generating pathways (28,29).…”
Section: Discussionsupporting
confidence: 92%
“…Increasing evidence suggests that the intracellular distribution of cGMP is not uniform, but rather is compartmentalised within cells, and this may underlie the differential effects of cGMP generated by soluble and particulate guanylyl cyclases [3]. The diverse effects of stimulating cGMP production in cardiovascular tissues are dependent on its binding to at least three groups of proteins: cGMPdependent protein kinase (or protein kinase-G; PKG), cGMP-regulated phosphodiesterases (PDEs) and cyclic nucleotide-gated ion channels [4].…”
Section: The Cyclic Guanosine Monophosphate Signalling Pathwaymentioning
confidence: 99%
“…FRETbased cGMP indicators are also limited in resolving possible compartmentalized intracellular cGMP signaling events using confocal microscopy. It was recently suggested that in VSM cells and cardiac myocytes cGMP signaling may be spatially segregated and that this functional compartmentalization may be the cause of the unique actions of ANP and NO (19)(20)(21)(22)(23). The goal of this study was to develop previously undescribed non-FRET biosensors suitable to monitor the temporal changes of [cGMP] i in response to low-nanomolar NO or ANP, and to investigate the spatial patterning of [cGMP] i , using real-time, confocal imaging techniques.…”
mentioning
confidence: 99%